2023
DOI: 10.3390/tropicalmed8020125
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Approaches for the Identification of Aptamer Binding Interactions to Leptospira spp. Cell Surface Proteins

Abstract: Aptamers are nucleic acids that can bind with high affinity and specificity to a range of target molecules. However, their functionality relies on their secondary and tertiary structures such that the combination of nucleotides determines their three-dimensional conformation. In this study, the binding mechanisms of candidate aptamers and their interactions with selected target proteins found in the cell surface of Leptospira were predicted to select high-affinity aptamers. Four aptamers were evaluated through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The phosphate groups in aptamers generally act as hydrogen bond acceptors, and the side chains of proteins serve as hydrogen bond donors. 46,47 Besides, owing to the negatively charged phosphate backbones, aptamers can attract the positively charged surface of target proteins, thereby inducing electrostatic interactions. 48,49 The hydrophobic interaction of aromatic rings with the aliphatic side chains of proteins is reported to be another force responsible for aptamer−target protein interactions.…”
Section: Regulation Methods Of Aptamer−protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphate groups in aptamers generally act as hydrogen bond acceptors, and the side chains of proteins serve as hydrogen bond donors. 46,47 Besides, owing to the negatively charged phosphate backbones, aptamers can attract the positively charged surface of target proteins, thereby inducing electrostatic interactions. 48,49 The hydrophobic interaction of aromatic rings with the aliphatic side chains of proteins is reported to be another force responsible for aptamer−target protein interactions.…”
Section: Regulation Methods Of Aptamer−protein Interactionsmentioning
confidence: 99%
“…In addition to nucleic acid bases, phosphate groups also play an important role in the formation of hydrogen bonding. The phosphate groups in aptamers generally act as hydrogen bond acceptors, and the side chains of proteins serve as hydrogen bond donors. , Besides, owing to the negatively charged phosphate backbones, aptamers can attract the positively charged surface of target proteins, thereby inducing electrostatic interactions. , The hydrophobic interaction of aromatic rings with the aliphatic side chains of proteins is reported to be another force responsible for aptamer–target protein interactions. , In addition, aromatic rings are also confirmed to participate in π–π stacking, mainly due to the overlapping of π orbitals. The final important binding interaction is the van der Waals force arising from the mutual attraction of dipoles and induced dipoles . It has been reported that the strength of van der Waals forces heavily depends on the dimension of the interacting interface .…”
Section: Regulation Methods Of Aptamer–protein Interactionsmentioning
confidence: 99%